The Business and Management of Ocean Cruises 2011
DOI: 10.1079/9781845938451.0003
|View full text |Cite
|
Sign up to set email alerts
|

The demand for ocean cruises - three perspectives.

Abstract: This chapter aims to contribute to a richer and more complex understanding of the demand for ocean cruises than that usually offered in industry studies and market research reports. Three perspectives on cruise demand are presented. The first perspective is largely quantitative and focuses on volumes, prices, distributions and time paths. It corresponds to the perspective conveyed by many market studies. The second perspective on cruise demand is psychological, emphasizing in particular two aspects that are ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…This is significantly more than the 1200-1300 kg estimated by Eijgelaar [11] or Carnival's 1067 kg CO 2 (considering 10.5 Mt of fuel and 9.8 Mio passengers). Assuming a worldwide average of 7 days for a cruise (slightly shorter for North Americans and longer for Europeans; [59]), passenger per day emissions would amount to around 239 kg CO 2 on the basis of IMO data [1]. However, a reason for the comparatively high figure in the IMO study could be that auxiliary engines have been added for both diesel electric and "geared systems" without subtracting it from total MCR, which, as this paper shows, could lead to an overestimation of fuel consumption on the order of 50%.…”
Section: Discussionmentioning
confidence: 99%
“…This is significantly more than the 1200-1300 kg estimated by Eijgelaar [11] or Carnival's 1067 kg CO 2 (considering 10.5 Mt of fuel and 9.8 Mio passengers). Assuming a worldwide average of 7 days for a cruise (slightly shorter for North Americans and longer for Europeans; [59]), passenger per day emissions would amount to around 239 kg CO 2 on the basis of IMO data [1]. However, a reason for the comparatively high figure in the IMO study could be that auxiliary engines have been added for both diesel electric and "geared systems" without subtracting it from total MCR, which, as this paper shows, could lead to an overestimation of fuel consumption on the order of 50%.…”
Section: Discussionmentioning
confidence: 99%
“…The growth rate of cruise passenger numbers has been stagnating over the past years, suggesting that the sector is approaching the maturity stage of its life-cycle, at least in its traditional source markets (Vogel and Oschmann, 2012;Weeden et al, 2011). While this contention may appear somewhat contradictory to the sector's published growthforecasts, a closer examination of their methodological aspects and key assumptions warranties scepticism towards their validity (Haahti et al, 2013, p. 129;Papathanassis and Vogel, 2012;Kollwitz and Papathanassis, 2011).…”
Section: Future Perspective: 75 Years and Beyondmentioning
confidence: 99%
“…The greatest growth in this sector, however, is in the amount of information being shared, both by firms and by customers (CLIA, 2016). Vogel and Oschmann (2012) questioned whether this phenomenon is truly promising, given that cruise prices have decreased in the past decade and competitors must continually reinvent themselves to offer memorable tourist experiences.…”
Section: Cruise Tourism Agendamentioning
confidence: 99%
“…Nevertheless, various factors have been found to influence tourists' intentions to take a cruise. Initial investigations have centered on economic, institutional and cultural environments (Vogel and Oschmann, 2012) leading to a definition of segments based on prices (Petrick et al, 2006;Satta et al, 2016) and destinations (Field et al, 1985). Beyond this context, Hung and Petrick (2011) found that passengers' intentions to take cruises could be influenced by a wider set of personal and emotional factors, such as the opportunity to escape from their everyday environment, relax, improve relationships with family, engage in social interaction and enjoy novel and luxurious experiences (Huang and Hsu, 2009).…”
Section: Cruise Tourism Agendamentioning
confidence: 99%